Assessing the impacts of flooding on vegetation cover in the Shashe-Limpopo confluence area using earth observation data - Gangashe, Andani Theophenia (My University, 2018)
The extensive and frequent flood events in the Shashe-Limpopo confluence area provide an opportunity to investigate the impacts of such an extreme event in terms of vegetation cover. Extreme flooding events are expected to occur more frequently as a consequence of climate change. Understanding the impacts of flood events on vegetation dynamic would be very useful to develop a dynamic simulation model that can predict the woody species composition of water retention areas or restored floodplains on the basis of flooding characteristics and therefore proposed riverine forest and landscape planning and management. This study used Landsat 7 data to quantify the response of vegetation to flood events in the Shashe-Limpopo confluence area. Two flood events that occurred in 2000 and 2013 respectively were analysed to evaluate the patterns of vegetation response in the area of study. Different indices such as NDVI, NDWI and Modified NDWI (MNDWI) were tested in mapping vegetation patterns and the flood extent. The MNDWI was shown to be more effective in extracting water information than the NDWI. NDVI results and change detection statistical change showed efficiency in indicating vegetation response to floods. The results show that using MNDWI and a 0.2 threshold value, water delineation is possible. Vegetation shows that it flourishes after the floods however; there is some degree of change. The results derived from this can be able to help with landscape planning and management.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science (Geography and Environmental Studies) at the School of Geography, Archaeology & Environmental Studies. Johannesburg, 24 February 2018.
Keywords: Conservation and natural resources; Floods; Remote sensing; Sand dune ecology--South Africa